2023
DOI: 10.1186/s12920-023-01692-8
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationships between blood lipids and major psychiatric disorders: Univariable and multivariable mendelian randomization analysis

Bozhi Li,
Yue Qu,
Zhixin Fan
et al.

Abstract: Background Whether the positive associations of blood lipids with psychiatric disorders are causal is uncertain. We conducted this two-sample Mendelian randomization (MR) analysis to comprehensively investigate associations of blood lipids with psychiatric disorders. Methods Univariable and multivariable models were established for MR analyses. Inverse variance-weighted (IVW) MR was employed as the main approach; weighted median and MR-Egger were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…What we also consider a novel finding in our study is a greater proportion of patients with psychological disorders requiring medical attention in the low LDL-C group. A recent study [24] found that higher LDL-C levels were associated with a lower risk of major depressive disorder (MDD), whereas one relatively recent case-control study found that higher LDL-C and total cholesterol levels and lower HDL-C levels were connected to anxiety disorder risk [25]. There are numerous gaps in our understanding of the role of cholesterol and its biosynthesis, so at this moment we could only suggest reasons for the described connection between "spontaneous" low LDL and psychological disorders in ACS patients [26].…”
Section: Discussionmentioning
confidence: 98%
“…What we also consider a novel finding in our study is a greater proportion of patients with psychological disorders requiring medical attention in the low LDL-C group. A recent study [24] found that higher LDL-C levels were associated with a lower risk of major depressive disorder (MDD), whereas one relatively recent case-control study found that higher LDL-C and total cholesterol levels and lower HDL-C levels were connected to anxiety disorder risk [25]. There are numerous gaps in our understanding of the role of cholesterol and its biosynthesis, so at this moment we could only suggest reasons for the described connection between "spontaneous" low LDL and psychological disorders in ACS patients [26].…”
Section: Discussionmentioning
confidence: 98%